2020
DOI: 10.1002/adfm.201908427
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase Exfoliated Indium Selenide Based Highly Sensitive Photodetectors

Abstract: Layered semiconductors of the IIIA-VIA group have attracted considerable attention in (opto)electronic applications thanks to their atomically thin structures and their thickness-dependent optical and electronic properties, which promise ultrafast response and high sensitivity. In particular, 2D indium selenide (InSe) has emerged as a promising candidate for the realization of thin-film field effect transistors and phototransistors due to its high intrinsic mobility (>10 2 cm 2 V −1 s −1 ) and the direct optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 101 publications
1
55
0
Order By: Relevance
“…[ 21 ] We found a field‐effect differential mobility of the film (μ fe —defined in the linear region, V D < V G – V th , of the I D – V G curve in Figure 3d) of ≈10 –3 cm 2 V −1 s −1 for a V G in the range between −40 and 0 V. We attribute the decrease in mobility compared to single flake values to the presence of traps and surface oxidation caused by the spray deposition processing in air, which increases the contact resistance between the interconnected flakes. [ 85,146 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 21 ] We found a field‐effect differential mobility of the film (μ fe —defined in the linear region, V D < V G – V th , of the I D – V G curve in Figure 3d) of ≈10 –3 cm 2 V −1 s −1 for a V G in the range between −40 and 0 V. We attribute the decrease in mobility compared to single flake values to the presence of traps and surface oxidation caused by the spray deposition processing in air, which increases the contact resistance between the interconnected flakes. [ 85,146 ]…”
Section: Resultsmentioning
confidence: 99%
“…The presence of carrier generation, trapping, and recombination processes within the ε‐GaSe can be studied by the power dependence of the photodetector. [ 85,147 ] In fact, an ideal thin‐film photodetector has a wide linear dynamic range, [ 154–157 ] in which the photocurrent I ph is proportional to the incident light power ( I ≈ P ϑ —with the power exponent ϑ = 1). [ 85,147 ] However, in the ε‐GaSe phototransistor, a nonunity exponent of 0 < ϑ < 1 was found that we assign to charge carrier trapping.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations